Multi-agent intelligent and autonomous co-space robotics system - Yu, Guo Hua. (2010)
This report will outline the project on Multi-agent Intelligent & Autonomous Co-Space Robotics System. Nowadays, robots are playing an important role in electrical engineering research and education. So the core development for this project is to build a Co-Space robotics system between physical and virtual robots. And this project involves developing a physical robotic system base on one microchip controller board. This controller board is used for sensor interfacing and motor controlling. And it also includes developing a virtual robot using Microsoft Robotics Developer Studio 2008. The ZigBee wireless communication links between these physical and virtual robotics system. It transfers the sensors and locomotion data between these two systems.